Quranic revelation as the word of God in a human discourse: Anthropological approach - Khorchide, Mouhanad (Münster journal for Islamic and philosophical studies, 2022)
This paper deals with the concept of revelation in the Islamic context as the word of God in a human discourse‭, ‬in an attempt to‭ ‬redefine revelation by adopting the concept of freedom and mercy‭. ‬Thus‭, ‬it seeks to overcome a dual epistemological dilemma that resulted from the Islamic tradition approach and the philological historical approach‭. ‬Therefore‭, ‬the paper deal with the following issues‭: ‬What is the reasonability of talking about the divine manifestation regardless of the contexts in which it occurs‭?‬‭ ‬Is revelation a cognitive necessity or just a reminder of rational knowledge‭? ‬And how is the divine manifestation carried out according to the Islamic vision‭? ‬The first question relates to an epistemological issue that deals with the conditions for the possibility of realizing religious knowledge based on revelation‭; ‬as for the second question‭, ‬it fundamentally deals with the relationship between religion and reason‭, ‬relying on the concepts of freedom and mercy as essential pillars in the redefinition of revelation‭; ‬while I seek in the last question to present a new approach that enables the redefinition of revelation as a divine manifestation‭, ‬and to relate this attempt to our present time by using a hermeneutic approach to the Qur’an‭.‬